Changes in the strength of the Nordic Seas Overflows over the past 3000 years - Moffa-Sanchez, P; Hall, IR; Thornalley, DJR; Barker, S; Stewart, C (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The Nordic Seas Overflows constitute the densest component of the deep limb of the Atlantic Meridional Overturning Circulation (AMOC). Changes in the vigour of the overflows may have had important climatic effects in the past and may also have in the future. Yet, evidence for multidecadal to millennial changes in the deep limb of the AMOC and their potential relationship to North Atlantic climate variability during the Holocene remains weakly constrained. Here we present grain size data, as a proxy for near-bottom current speed, from sub-decadal to decadally resolved sediment cores located in the direct pathway of the two Nordic Overflows east and west of Iceland, the Iceland-Scotland Overflow Water (ISOW) and the Denmark Strait Overflow Water (DSOW), respectively. The results show no clear relationship between reconstructed changes in the vigour of the Nordic Overflows and the well-known periods of centennial-scale climate variability recorded in the North Atlantic region. However, well-defined millennial-scale trends are found in both of the overflow strength records over the last 3000 years, which were possibly related to hydrographic reorganizations in the Nordic Seas, driven by the decrease in Northern Hemisphere summer insolation over the Neoglacial period. A comparison between the near-bottom flow speed reconstructions from ISOW and DSOW suggests an anti-phased relationship between the Nordic Seas Overflows east and west of Iceland over the last 3000 years. This feature has been observed in climate models potentially as a result of shifts in the deep water formation sites as a response to changes in atmospheric patterns over the Nordic Seas.